As perspectivas do plebiscito e do referendo no Brasil após a promulgação da Emenda Constitucional n. 111/21, a partir das “ballot measures” do direito norte-americano - Queiroz, Victor Oliveira (2023)
The aim of this work is to analyze the perspectives of plebiscite and referendum in Brazil after the legal change occurred by the Brazil Constitutional Amendment n. 111/221. This amendment has reformed Brazil’s constitutional text in order to add the paragraphs twelve and thirteen to the fourteenth article. It says about the possibility to accomplish local popular consultations simultaneously to the local elections, starting 2024, as long as they are initiated by the City Council about local issues, previously notified to the Electoral justice by ninety days prior to the elections. In order to amplify the understanding about the matter, it was compared the Brazilian system to the United States’ one, towards the use of ballot measures. This instrument of popular participation over one-century settled in the US and that implies the people’s consultation about relevant state or local issues simultaneously to the elections. It was initiated the discussion with the concept of democracy and its classification according to Brazilian doctrine (direct, representative and participative). After, it is shown how participative democracy is established in Brazil’s 1988 Constitution, analyzing also plebiscite, referendum and popular initiative, their concepts and historical use. Afterwards it was outlined a legal overview about the plebiscite and referendum in Brazil, examining the articles of Brazilian law’s n. 23.385/12 and the Tribunal Superior Eleitoral’s Resolution n. 23.385/12, besides the constitutional changes of Constitutional Amendment n. 111/21. Right after, for a better understanding about the issue, it was studied U.S democracy, its organization and its popular participation mechanisms (recall, petitions, town-meetings). It was studied about the ballot measures, its concept, its legal nature, classifying it (Citizen Initiated and Legislative Referral). It was exanimated the use of ballot measures in the recent American elections. This work was finished bringing forward a possible legal and organizational panorama about how plebiscite and referendum will probably work in Brazil after Constitutional Amendment n. 111/21. It was extracted three essential lections about the impacts of constant use of ballot measures in America, such as public policy guidance, social impact and direct effect towards popular participation. It was perceived three challenges that currently plebiscite and referendum face in Brazil and that could prevent the constant use of this mechanisms. It was concluded with one answer proposition to each one of those three challenges, in order to enable the strengthening of these participative Democracy’s instruments in Brazil.